2021
DOI: 10.3892/ijmm.2021.4934
|View full text |Cite
|
Sign up to set email alerts
|

Silencing microRNA‑29b‑3p expression protects human trabecular meshwork cells against oxidative injury via upregulation of RNF138 to activate the ERK pathway

Abstract: In recent years, the potential involvement of numerous microRNAs (miRNAs) in glaucoma has been widely reported. However, the role of microRNA-29b-3p (miR-29b-3p) in the pathogenesis of glaucoma remains unknown. This study aimed to explore the biological role and regulatory mechanism of miR-29b-3p in the oxidative injury of human trabecular meshwork (HTM) cells induced by H 2 O 2 stimulation. By establishing a glaucoma rat model, the effects of miR-29-3p in glaucoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In vivo, miR-29 was found to be downregulated in the retina of a CNS-injury-induced model of glaucoma [ 126 ]. Contradictory to other reports, Liu et al demonstrated reduced miR-29b expression in the retinal tissues of glaucoma rats vs. control [ 127 ]. In addition, they suggested that miR-29b may induce apoptosis in human TM cells and silencing of miR-29 protected HTM cells against oxidative injury via ERK pathway.…”
Section: Mir-29 Family In Glaucomamentioning
confidence: 92%
“…In vivo, miR-29 was found to be downregulated in the retina of a CNS-injury-induced model of glaucoma [ 126 ]. Contradictory to other reports, Liu et al demonstrated reduced miR-29b expression in the retinal tissues of glaucoma rats vs. control [ 127 ]. In addition, they suggested that miR-29b may induce apoptosis in human TM cells and silencing of miR-29 protected HTM cells against oxidative injury via ERK pathway.…”
Section: Mir-29 Family In Glaucomamentioning
confidence: 92%
“…For example, identifying miRNAs that target genes involved in oxidative stress, neuroinflammation, and retinal ganglion cell apoptosis can help unravel the molecular pathways underlying glaucoma development and progression [47,86,127]. Functional studies such as in vitro experiments or animal models can provide valuable information on the role of specific miRNAs in glaucoma pathophysiology [128,129].…”
Section: Limited Understanding Of Functional Significancementioning
confidence: 99%
“…Silencing of miR-29b-3p could protect human trabecular meshwork cells against oxidative injury by upregulation of RNF138 to activate the extracellular signal-regulated kinase pathway (Ref. 31).…”
Section: Oxidative Stress-related Eye and Brain Diseasesmentioning
confidence: 99%